1994
DOI: 10.3758/bf03213891
|View full text |Cite
|
Sign up to set email alerts
|

Key membership and implied harmony in Western tonal music: Developmental perspectives

Abstract: We investigated the role of key membership and implied harmony in adults' and children's perception of tone sequences. Listeners were evaluated on their ability to detect three types of changes in one note of a well-structured Western tonal melody. In one change (out-of-key) the new note was not in the basis key, in another (out-of-harmony) it was in the key but not in the implied harmony, and in the third (within-harmony) it was in both the key and the implied harmony. Adults and 7-year-olds performed better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 46 publications
11
138
1
2
Order By: Relevance
“…Previous research provides unequivocal evidence that music perception and performance abilities are influenced by maturity and increased exposure to music. For example, before puberty, children's perception of tone patterns is relatively culture free (Andrews & Dowling, 1991;Dowling, 1990;Krumhansl & Keil, 1982;Lynch, Eilers, Oller, & Urbano, 1990;Schellenberg, 2001;Trainor & Trehub, 1994;Trehub, Schellenberg, & Kamenetsky, 1999), although formal training in music accelerates the enculturation process (Morrongiello, 1992). Music performance abilities also improve with age and continued practice (Davidson, 1985;Dowling, 1984;Hargreaves, 1986;Howe, Davidson, & Sloboda, 1998;Miller, 1987).…”
Section: Comparing the Modelsmentioning
confidence: 99%
“…Previous research provides unequivocal evidence that music perception and performance abilities are influenced by maturity and increased exposure to music. For example, before puberty, children's perception of tone patterns is relatively culture free (Andrews & Dowling, 1991;Dowling, 1990;Krumhansl & Keil, 1982;Lynch, Eilers, Oller, & Urbano, 1990;Schellenberg, 2001;Trainor & Trehub, 1994;Trehub, Schellenberg, & Kamenetsky, 1999), although formal training in music accelerates the enculturation process (Morrongiello, 1992). Music performance abilities also improve with age and continued practice (Davidson, 1985;Dowling, 1984;Hargreaves, 1986;Howe, Davidson, & Sloboda, 1998;Miller, 1987).…”
Section: Comparing the Modelsmentioning
confidence: 99%
“…As a result, this paradigm is only able to indicate how transpositions interfere with the subject's judgment of the structural identity of the melodies-that is, it provides only indirect information regarding the effect of transposition on the perceived similarity. Moreover, the introduction of an altered tone introduces an additional variable that may strongly influence a listener's judgment, depending on the position ofthe altered tone in the melody and the type of (diatonic or chromatic) alteration (see, e.g., Bharucha, 1984a;Trainor & Trehub, 1994;van Egmond & Povel, 1996). In contrast, the similarity comparison paradigm used in this study does not have to introduce lures (and, consequently, an additional variable) but obtains a direct estimate ofthe similarity between different transpositions that are created by manipulating the variable(s) under investigation.…”
Section: Similarity Judgments On Transposed Tonal Melodiesmentioning
confidence: 99%
“…Trainor and Trehub (1994) found that both 5-yearolds and 7-year-olds demonstrated knowledge of key membership by easily detecting changes in a melody that went outside the key. However, they found that harmonic knowledge appears to develop later; 7-year-olds better detected changes that remained within the key but violated implied harmonic structure compared to 5-year-olds.…”
Section: Young Children Pause On Phrase Boundariesmentioning
confidence: 99%